(untitled) (Research, Society and Development, 2022)
Objective: to describe deaths from acute myocardial infarction/Ba, between the years 2016 to 2020, according to sociodemographic characteristics and place of occurrence. Methods: ecological study, carried out with data from the Department of Informatics of the Unified Health System (DATASUS), whose population consisted of deaths recorded in the Mortality Information System (SIM). Results: a total of 126 deaths from AMI were found, from 15 in 2016 to 31 deaths in 2020. The year with the lowest mortality was in 2016 and 2019 the highest number of deaths. The distribution by sex reveals a predominance of males with a total of 72 cases (57.1%), however it also covers women with 54 cases (42.9%). In the first years diagnosed, especially men, hospital age of 80 years and over, with low education, of mixed color, married and three mainly marked in the environment. Conclusion: it is necessary to promote and prevent health actions on diseases that progress to cardiovascular diseases, such as DM and SAH. Scientific research is crucial to stimulate the improvement of the quality of life of people in the risk group for the development of pathologies of a cardiac nature.